2011
DOI: 10.1007/s13355-011-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of humidity on the infection of western flower thrips, Frankliniella occidentalis (Thysanoptera: Thripidae), by Beauveria bassiana

Abstract: The insecticidal activity of Beauveria bassiana GHA derived from a commercial mycoinsecticide BotaniGard ES against Frankliniella occidentalis was determined in a bioassay by dipping the female adults into a conidial suspension. The 90% lethal concentration of B. bassiana GHA was estimated to be 9.7 9 10 6 conidia/ml. The lethal times for achieving 90% mortality of thrips inoculated with a 1/500-diluted solution of BotaniGard ES and a 10 7.5 (3.16 9 10 7 ) conidia/ml suspension of B. bassiana GHA were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Previous experiments on F. selysi found that, for the S2 strain of B. bassiana that we collected from our field site, this concentration resulted in intermediate mortality rates (Reber and Chapuisat, in press). A similarly high concentration of conidia has also been used in other studies on the response of different insects to B. bassiana (e.g., Castilho et al 2010;Mukawa et al 2011). The first callow worker from each rearing group was randomly assigned to either the fungal exposure or the control treatment.…”
Section: Callow Survival and Fungal Challengementioning
confidence: 99%
“…Previous experiments on F. selysi found that, for the S2 strain of B. bassiana that we collected from our field site, this concentration resulted in intermediate mortality rates (Reber and Chapuisat, in press). A similarly high concentration of conidia has also been used in other studies on the response of different insects to B. bassiana (e.g., Castilho et al 2010;Mukawa et al 2011). The first callow worker from each rearing group was randomly assigned to either the fungal exposure or the control treatment.…”
Section: Callow Survival and Fungal Challengementioning
confidence: 99%
“…The present study also showed that the efficacy of new native strains was significantly higher than that of the reference strain GHA which caused intermediate mortality of L. decemlineata adults. GHA strain, the active ingredient of mycopesticide BotaniGard ® WP, has been reported to be highly efficient in the control of many arthropod pests [70][71][72][73][74]. This strain was originally isolated from a chrysomelid beetle Diabrotica undecimpunctata Mannerheim (Coleoptera: Chrysomelidae) and host specificity thus might be one of the reasons why it was less effective compared to native strains isolated from naturally infected CPB adults.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with other mite species reported promising results for B. bassiana against P. latus in laboratory bioassays and greenhouse trials (Peña et al 1996) and with various fungal isolates against the false spider mite, Brevipalpus phoenicis (Geijskes) (Acari: Tenuipalpidae) under laboratory conditions (Rossi-Zalaf & Alves 2006). The strain GHA has been reported to be highly efficient in control of many insect pest species (Liu & Bauer 2008;Mukawa et al 2011;Clavet et al 2013;Parker et al 2015) and was found to be virulent also against T. urticae (Ullah & Lim 2015). In the present study, however, the efficacies of all tested Beauveria spp.…”
Section: Discussionmentioning
confidence: 99%